Communicating women’s health: Social and cultural norms that influence health decisions - Gatison, A.M. (Communicating Women’s Health: Social and Cultural Norms that Influence Health Decisions, 2015)
This volume explores the conditions under which women are empowered, and feel entitled, to make the health decisions that are best for them. At its core, it illuminates how the most basic element of communication, voice, has been summarily suppressed for entire groups of women when it comes to control of their own sexuality, reproductive lives, and health. By giving voice to these women’s experiences, the book shines a light on ways to improve health communication for women. Bringing together personal narratives, key theory and literature, and original qualitative and quantitative studies, the book provides an in-depth comparative picture of how and why women’s health varies for distinct groups of women. Organized into four parts-historical influences on patient and provider perceptions, breast cancer the silence and the shame, make it taboo: mothering, reproduction, and womanhood, and sex, sexuality, relational health, and womanhood-each section is introduced with a brief synthesis and discussion of the key questions addressed across the chapters. © 2016 Taylor & Francis.
Keywords: dept.com

Epilogue - Gatison, A.M. (Communicating Women’s Health: Social and Cultural Norms that Influence Health Decisions, 2015)
Keywords: dept.com

Introduction: Social, cultural norms and women’s health - Gatison, A.M. (Communicating Women’s Health: Social and Cultural Norms that Influence Health Decisions, 2015)
In 2002, the Institute of Medicine published Unequal Treatment: Confronting Racial and Ethnic Disparities in Health Care, which reported that racial and ethnic minorities experience a lower quality of healthcare than nonminorities, even when they have income and insurance. That report pointed to stereotyping and bias within the healthcare system as the primary culprit and made recommendations about developing culturally competent healthcare as the fundamental way to reduce health disparities. Since then, cultural competency in health communication has become the touchstone for targeted health communication and disease prevention efforts for women and minorities. Unfortunately, this goal will never be achieved unless we hear from the women who continue to fall through the cracks of the still-broken healthcare system. Indeed, in the 21st century, there remain social and cultural norms that manifest themselves via institutional and interpersonal barriers to effective health communication along the lines of race, class, gender, ethnicity, and sexuality that unduly impact women as a group. These social and cultural norms are defined as a pattern of behavior in a particular group, community, or culture, accepted as normal and to which an individual is expected to conform. © 2016 Taylor & Francis.
Keywords: dept.com

The Pink and Black Experience: Lies That Make Us Suffer in Silence and Cost Us Our Lives - Madlock Gatison, A. (Women's Studies in Communication, 2015)
Keywords: dept.com; peer-reviewed